Pengaruh Kontrol Glikemik dengan Konversi Sputum BTA pada Pasien Diabetes Melitus dengan Tuberkulosis - Septa, Della; Surjadi, Lily Marliany (Fakultas Kedokteran Universitas Trisakti, 2023)
Background Diabetic people have a 2-3 times higher risk of tuberculosis than non-diabetic people. Immunocompromised conditions due to diabetes increase the risk of therapeutic failure and delayed sputum conversion, which may cause by poor glycemic control. This study was conducted to determine the glycemic control effect on AFB conversion in diabetic patients with tuberculosis. Methods A cross-sectional study has been conducted on 100 diabetic patients with the new emergence of pulmonary tuberculosis. All patients were in intensive phase treatment of tuberculosis for two months at Bhayangkara R. Said Sukanto's Hospital. Data collected from medical records were random blood glucose level, percentage of random blood glucose decrement, HbA1C, and the microscopic AFB sputum smear. Fisher exact test analysis was conducted to determine the effect of random blood glucose level, percentage of blood glucose decrement and HbA1C to AFB smear results using SPSS V25.0 software for Windows with a significance level of 0.05. Results The analysis between glycemic control and AFB sputum smear conversion using random blood glucose, percentage of random blood glucose decrement and HbA1C showed a p-value of 0.000, indicating a significant relationship (p<0.05), so it showed that glycemic control affects AFB sputum smear conversion. Conclusions A significant relationship exists between glycemic control and AFB-negative conversion in patients with DM and TB. RBG showed the best sensitivity and specificity as a glycemic control parameter compared to others.